Evaluating coastal agroecological dynamics using Landsat-derived vegetation and environmental indices embedded in Decision Support System and Monitoring Tools: insights from Guyana towards achieving SDGs - Esan Ayeni Hamer; Temitope D. Timothy Oyedotun; Gordon A. Nedd (Discover Sustainability)
Abstract Coastal agroecological zones are vital for ensuring ecological stability, food security, and economic resilience. However, these zones face escalating threats from climate change, including salinity intrusion, vegetation degradation, and disruptions to hydrological processes. This study evaluates the dynamics of vegetation health, soil salinity, and water availability within Guyana’s coastal agroecological zones using multi-temporal Landsat 8 imagery, spectral indices such as the Enhanced Vegetation Index (EVI), Modified Soil-Adjusted Vegetation Index (MSAVI), Normalized Difference Salinity Index (NDSI), and Normalized Difference Water Index (NDWI), and a customised Decision Support System (DSS) for environmental monitoring and planning. Spanning 2015–2023, the sample application analysis focuses on the Mahaica-Berbice region (Region 5) of Guyana, a critical rice-farming area, to identify spatial and temporal trends, assess climate impacts on biogeochemical cycles, and provide actionable insights. This study integrates Google Earth Engine (GEE) for scalable geospatial analysis and a DSS that synthesises environmental indices into interactive, actionable formats for policymakers. The DSS offers an innovative platform for monitoring agroecological dynamics, identifying vulnerable zones, and guiding adaptive management strategies. Results reveal substantial annual variations in vegetation health, salinity, and water content, emphasising climate-induced vulnerabilities and their implications for carbon and nitrogen cycling. These findings emphasise the importance of sustainable resource management strategies and reinforce resilience against climate-induced challenges. The study directly supports the United Nations Sustainable Development Goals (SDGs), including SDG 2 (Zero Hunger) by advancing sustainable agriculture, SDG 13 (Climate Action) by fostering adaptive climate strategies, and SDG 15 (Life on Land) by promoting biodiversity conservation and ecosystem health. By combining remote sensing, DSS innovation, and environmental monitoring tools, this research offers a replicable, evidence-based framework to balance development and ecological sustainability in vulnerable coastal landscapes. It demonstrates the critical role of integrated technologies in shaping climate-resilient futures. Clinical trial registration: Not applicable.